2010
DOI: 10.1007/s13258-009-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversification of 45S rRNA ITS, trnH-psbA spacer, and matK genic regions in several Allium species

Abstract: Allium is a very diverse genus with over 600 species distributed worldwide. Haplotype analyses of 45S rRNA ITS, trnH-psbA spacer, and matK gene sequences in 9 Allium species were carried out, subsequent to which phylogenetic relations of the nine species were also analyzed. Of the three genes, the nuclear 45S rRNA ITS sequences showed the highest variation with one haplotype in each species. The other two chloroplast genes revealed that more than one haplotype was present in each species, and each haplotype wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Genetic relationships among 9 Allium species were recently analyzed using the polymorphisms within the nucleotide sequences of trnH-psbA, ITS, and matK (Son et al, 2010). The authors reported the presence of more than 1 haplotype in both organellar and nuclear genomes in a single plant of the Allium species, which makes phylogenetic analysis and barcoding impossible using the nucleotide sequences of these DNA regions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic relationships among 9 Allium species were recently analyzed using the polymorphisms within the nucleotide sequences of trnH-psbA, ITS, and matK (Son et al, 2010). The authors reported the presence of more than 1 haplotype in both organellar and nuclear genomes in a single plant of the Allium species, which makes phylogenetic analysis and barcoding impossible using the nucleotide sequences of these DNA regions.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all three species of Physacanthus showed molecular evidence of the hypothesized wide hybridization event and that the three species in the genus are morphologically cohesive (i.e., they share the defining morphological feature of inflated calyces, Figures 2, S3) argues that the hybridization event occurred prior to speciation, giving rise to the common ancestor of the three species, Similar lines of evidence were used to argue that establishment of organellar heteroplasmy preceded species diversification in Allium [47]. The alternative hypothesis of re-establishing heteroplasmy every generation via hybridization seems extremely implausible (and would require that parental sources of both chloroplast lineages remain in sympatry), especially given that modern geographic ranges of the three species of Physacanthus are distinct.…”
Section: Resultsmentioning
confidence: 67%
“…In a previous study, the matk gene was proposed for resolving phylogenetic associations in plant species (Abugalieva et al 2017;İpek et al 2014İpek et al Ito et al 1999Kim et al 2018;Son et al 2010). The genes utilized for DNA barcoding in plant populations include matK, rpoC1, rpoB, trnH-PsbA, rbcL, atpF-atpH, psbK-psbI, and their combinations, of which, matK and rbcL were adopted as 2-locus DNA barcode by the CBOL Group (Hollingsworth et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…DNA sections were mostly discrete parts in Allium. Nevertheless, some species were not distinguishable from one another by the matK sites (Abugalieva et al 2017;Ince et al 2005;İpek et al 2014;Li et al 2011;Son et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation